Discovery of novel 3-isoxazolylvinylcephalosporins - Choi, II K. (1999)
[No abstract available]
Keywords: cefdinir; cefotiam; cefpirome; cefpodoxime; cephalosporin derivative; kst 150257; kst 150290; kst 150608; kst 150609; unclassified drug; antibiotic therapy; drug activity; drug screening; drug structure; drug synthesis; nonhuman; review